Labour market flexibility and its effect on worker’s rights and representation: a case study of food industries and the food federation and allied workers union of Zimbabwe. - Mariga, Ashford (Midlands State University, 2017)
This study explored the effects of labour market flexibility to workers’ rights and representation the case study being Harare food and allied industries and the Federation of Food and allied Workers Union.The research was predominantly influenced by the ever-increasing instability of Labour relations and the deterioration of workers representation and rights in Zimbabwean food industries. Capitalist, Keynes and the Classical theories served as the theoretical and conceptual framework to the study. An amalgamated exploratory design was used to assess, to identify, unravel reasons and effects of labour market flexibility to workers’ rights and representation in food industries, which included qualitative and quantitative approach. Fifty questionnaires were distributed among the NEC graded employees in the food and allied industries using stratified random sampling .In-depth interviews with the Federation of Food and Allied Workers Union of Zimbabwe staff using purposive sampling was used to obtain qualitative data. Data analysis and presentation of questionnaires was done using graphs and tables .Qualitative data from parts of the questionnaires and interviews was also hinged on thematic and content analysis. The research established that violation of workers’ rights and representation resulted from labour market flexibility.Measures like, changes in working hours, collective bargaining, trends in contracts of employment, trade union participation and membership were used to gauge the extent to which flexible labour markets affected workers rights. Flexibility to labour market has resulted in the conversion of permanent employees to become casual and fixed term contracts leaving them vulnerable to job losses and victimization at work. This also led to employers to take advantage and ignore the labour laws in altering and making changes in every line of employment relations thus crippling workers’ rights leaving thm insecure of their job lives. This has compromised the significance of trade unions since it ignored labour regulations, which is the backbone and a Broadway to the functions and duties of a trade Union the Federation of Food and Allied Workers Union of Zimbabwe lost almost half of its membership to labour market flexibility. The study concluded by recommending that there is need to revisit the labour legislations and statutes to consider and pay attention to the new prevailing labour situations .The study considered that a careful attention should be given on the powers and duties of an employer since they tend to abuse their privileges .